Neprilysin 2 catalyses the degradation of natriuretic peptides despite sacubitrilat Inhibition - Elizaveta M. Selezneva; Evgeniya E. Feygina; Liudmila V. Ageeva; Fedor N. Rozov; Irina V. Kopylova; Evgeny P. Altshuler; Alexander G. Semenov (Scientific Reports)
Abstract Neprilysin (NEP) cleaves active forms of A- and B-type natriuretic peptides (ANP and BNP) at multiple sites, reducing their compensatory effects in heart failure. Therapeutic inhibition of NEP by sacubitrilat may potentiate the beneficial effects of natriuretic peptides. Neprilysin 2 (NEP2), a close homolog of NEP, has been described in humans but remains poorly characterized. This study aimed to investigate NEP2 expression in the cardiovascular system, its ability to cleave natriuretic peptides, and its inhibition by sacubitrilat. NEP and NEP2 expression profiles were assessed using reverse transcription PCR. The efficiency of in vitro cleavage of ANP, BNP, and the BNP precursor proBNP by NEP and NEP2 recombinant soluble domains was evaluated using sandwich-type immunoassays using antibodies specific for novel proteolytic epitopes. Expression of both NEP2 and NEP was observed at the mRNA level in cardiomyocytes and endothelial cells. NEP2 cleaved ANP and BNP; however, it was insensitive to sacubitrilat at studied concentration. In contrast to NEP, we observed proBNP proteolysis by NEP2, which resulted in the formation of a truncated form (amino acid residues 5–32). Our results show that sacubitrilat-insensitive NEP2 mediates ANP and BNP proteolysis and therefore might reduce compensatory effects of natriuretic peptides in heart failure.